Problematika Pemanfaatan Buku Paket Pendidikan Agama Islam Sekolah Dasar di Kota Balikpapan - Abu Muslim (EDUKASI: Jurnal Penelitian Pendidikan Agama dan Keagamaan, 2016)
This research is aimed at acknowledging the effectiveness of utilizing elementary school Islamic Religion Education Textbooks in Balikpapan City. The focus of this research in the availability and utilization of as well as the problems faced in relation to the books. This research uses descriptive qualitative method. Data Collection was performed though interviews and observations. The collected data were then sorted based on research focus category for further in-depth analysis. The research results show that in Balikpapan city, the optimization of the utilization of Islamic Religion Education Books in Elementary Schools highly depends on the availability of compulsory and auxiliary books as the manifestation of the policies issued by the entire education apparatus, starting from stakeholders, education components, as well as public support. Curriculum selection also greatly affects the book utilization process. Because, in fact, the 2013 curriculum book distribution is not yet maximum. There is even a school deciding to return to the Education Unit Level Curriculum due to textbook availability, whereas the schools concerned is one of the pilot schools for the implementation of the 2013 curriculum in Balikpapan City. The aspect of supervision on distribution also becomes important in the context of supporting the achievement of the Islam religion education objective through the requirement-based book availability. However, in general, teachers and parents’ initiatives greatly support the maximization of the utilization of books as learning sources in Balikpapan City.